Electrode-modified block copoly-ionic liquid boosting the CO2 reduction toward CO in water-based media. Issue 16 (3rd February 2023) - Grammatico, Domenico; Marcasuzaa, Pierre; Viterisi, Aurelien; Bousquet, Antoine; Su, Bao-Lian; Billon, Laurent
Abstract : Selective CO2  reduction to CO is observed by a Block CoPolyIonicLiquids coating on immobilized Re-molecular catalyst, new concept paving the way of implementing solid Ionic Liquids as efficient building blocks to boost CO2 RR and suppress HER. Abstract : Coupling polymer and ionic liquids with electrodes for catalysis is a promising tool for optimization of electrocatalytic CO2 reduction reaction (CO2 RR). Here, block copolymer ionic liquids BCPILs were synthesized via controlled radical polymerization and nucleophilic post-substitution to introduce imidazole moieties. We show that, thanks to these PIL functionalities, the BCPIL/Re@HPC/GDL electrode can keep the selectivity toward CO when a higher amount of water is present in the electrolyte than the raw Re@HPC/GDL system. Our results help to understand the development of solid-state ionic liquids for enhanced CO2 RR in water-based electrolyte.